2
$\begingroup$

Example: Prove the ABSORPTION LAW: $$ x(x + y) = x $$

$ Solution: \\ x(x + y) \\ = (x + 0)(x + y) \;\;\;\;\; Identity \;Law \\ = x + (0 · y) \;\;\;\;\;\;\;\;\;\;\; Distributive \;Law \\ = x + y · 0 \;\;\;\;\;\;\;\;\;\;\;\;\;\; Commutative \;Law \\ = x + 0 \; \;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;Domination \;Law \\ = x \;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\; Identity \;Law \\ $

I was given an example here and shown one method of solving it. I was told there was an alternative solution to it and I was curious about it.

This is one method of proving the problem.

The alternative method suggested solving the same expression in the order of:

DISTRIBUTIVE LAW, IDEMPOTENT LAW, DISTRIBUTIVE LAW, DOMINANCE LAW, and IDENTITY LAW.

When I try, I get stuck here:

$ Solution: \\ x(x + y) \\ = (x · x) + (x · y) \;\;\;\;\; Distributive \;Law \\ = x + (x · y) \;\;\;\;\;\;\;\;\;\;\;\;\; Idempotent \;Law \\ = (x + x)(x + y) \;\;\;\;\;\; Distributive \;Law \\ $

I've been stuck on where I can prove it using the dominance law, unless I can extend this with an identity law proof. My first time in a while, please excuse.

$\endgroup$
2
$\begingroup$

Solution: $$ \begin{align}x(x+y) &= (x\cdot x)+(x\cdot y) \quad\text{[Distributive Law]} \\ &= x + (x\cdot y) \quad\text{[Idempotent Law]} \\ &= x \cdot (1+y) \quad\text{[Distributive Law]}\\ &= x \cdot 1 \quad\text{[Property of 1]} \\ &= x \quad\text{[Property of 1]} \end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.